Pengaruh Profesionalisme Personil terhadap Kualitas Pelayanan Logistik pada Dinas Material Korps Marinir Jakarta - Suparwan CK; Ratu Ratna Trisna; Datunabolon Datunabolon (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2018)
The Indonesian Navy materials’ sub unit is one of the main commands (KOTAMA) of the Indonesian Navy with the slogan “Jalesu Bhumyamca Jayamahe” which means “we are victorious in the sea and in the land.” The aim of the study is to analyse the effect of the materials sub unit employees’ professionalism to the logistics’ service quality in 2017. The method used was field and library research. The study used simple linear regression, coefficient correlation, coefficient determination, and hypothesis testing to analyse the data. The result shows that there is a significant effect between employees’ professionalism to the logistics’ service quality shown by the simple linear regression of Y=34,540 + 0.87 X. Based on the coefficient determination, there are some factors affect the service quality which are employees’ professionalism (90,25%) and facilities at work, discipline, work effective (9.75 %). The hypothesis also proves that t-count is more than t-table which Ho is rejected and Ha is accepted. It concludes that there is significant relation between both factors.